Faktor-Faktor Yang Berhubungan Dengan Inisiasi Menyusu Dini Di Wilayah Kerja Puskesmas Satelit Bandar Lampung - Nidya Aryani (LPPM Sikes Panca Bhakti Bandar Lampung, 2018)
Early Breastfeeding Initiation (IMD) is a process of allowing a baby with its own instinct to suckle immediately within an hour of birth, along with infant skin contact with mother's skin. The percentage of IMD is low in Indonesia in 2013 by 34.5% and Lampung Province by 23%. The purpose of this study was to determine factors related to IMD in the Work Area of Bandar Lampung Satellite Puskesmas. The type of this research is quantitative with cross sectional design, data collected primary data with interview technique with questionnaire instrument. The population in this study were mothers who had infants aged 0-3 months in the Work Area of Bandar Lampung Satellite Puskesmas and a sample of 168 people. The data were analyzed by univariate, bivariate with chi squared, and multivariate analysis with multiple logistic regression. The results showed that mothers who did IMD of 48.8%. Factors related to IMD were pregnancy plan (p value = 0,000; OR = 84.94), parity (p value = 0.013; OR = 7.02), husbands support (p value = 0,000; OR = 6, 88), support of health workers (p value = 0.043, OR = 4.68), and knowledge (p value = 0.013; OR = 4.29). Of the five variables the most dominant is the pregnancy plan variable (p value = 0,000; OR = 84.94). And the age variable (p value = 0.197; OR = 3.33) is the confounding variable. The recommendations of this research are health workers, especially midwives who work in the work area of Satellite Health Center to further improve mother counseling program especially about the benefits of IMD, the importance of breastfed babies, and the benefits of mother to implement IMD and health workers who help deliver to keep consistent IMD at every mother of birth.